HUBUNGAN ANTARA KONSEP DIRI DAN MOTIVASI BERPRESTASI DENGAN HASIL BELAJAR FISIKA PESERTA DIDIK SMA DI KOTA MAKASSAR - Qalsum, Ummi; Nurhayati, Nurhayati; Yani, Ahmad (Universitas Negeri Makassar, 2015)
This study aims to determine and describe the relationship between self-concept and achievement motivation in physics learning outcomes, either individually or jointly. Population is a Class XI student of High School and private accredited Makassar. The samples used were 340 people who are determined based on tables Isaac and Michael with proportionate stratified random sampling technique. Measurement of self-concept and achievement motivation using a Likert scale questionnaire instrument models with a range of scores 1-5. Physics learning outcomes are measured by the instruments of learning outcomes. To avoid errors of analysis and rank the twins then ordinal data from scores of self-concept and achievement motivation is converted into a scale interval using the formula Method Successive Interval (MSI). Data were analyzed by using simple regression, multiple regression, and correlation with significance level α = 0.05. The results showed (1) there is a positive relationship between self -concept and learning outcomes of Physics through regression equation Y=14.281+0.016X1 with a contribution of 3.6%; (2) there is a positive relationship between achievement motivation and learning outcomes of Physics through regression equation Y=13.146+0.029X2 with a contribution of 0.1%; (3) there is a positive relationship between self-concept and achievement motivation in physics learning outcomes through the regression equation Y=12.945+0.003X1+0.027X2 with a contribution of 54.2%. These results suggest that the self-concept and achievement motivation influence in favor of Physics student learning outcomes, but the impact that lower number of other factors that caused greater support Physics learning outcomes of learners.Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan hubungan antara konsep diri dan motivasi berprestasi dengan hasil belajar fisika, baik secara sendiri-sendiri maupun secara bersama-sama. Sampel yang digunakan berjumlah 340 orang yang ditentukan berdasarkan tabel Isaac dan Michael dengan teknik proportionate stratified random sampling. Pengukuran terhadap konsep diri dan motivasi berprestasi menggunakan instrumen angket model skala likert dengan rentangan skor 1-5. Hasil belajar Fisika diukur dengan instrumen hasil belajar. Data penelitian diolah dengan teknik regresi sederhana, regresi ganda, dan korelasi dengan taraf signifikansi α=0.05. Hasil penelitian menunjukkan (1) terdapat hubungan yang positif antara konsep diri dan hasil belajar Fisika melalui persamaan regresi Y=14.281+0.016X1 dengan kontribusi sebesar 3.6%; (2) terdapat hubungan yang positif antara motivasi berprestasi dan hasil belajar Fisika melalui persamaan regresi Y=13.146+0.029X2 dengan kontribusi sebesar 0.1%; (3) terdapat hubungan yang positif antara konsep diri dan motivasi berprestasi dengan hasil belajar Fisika melalui persamaan regresi Y=12.945+0.003X1+0.027X2 dengan kontribusi sebesar 54.2%. Hasil ini menunjukkan bahwa konsep diri dan motivasi berprestasi memberikan pengaruh dalam mendukung hasil belajar Fisika peserta didik namun pengaruh yang diberikan rendah diakibatkan banyaknya faktor lain yang lebih besar mendukung hasil belajar Fisika peserta didik.Kata Kunci:konsep diri, hasil belajar fisika, motivasi berprestasi